Black sea urchins evaluate predation risk using chemical signals from a predator and injured con- and heterospecific prey - Morishita, Vanessa Rimoli [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Inter-research, 2011)
The traits related to foraging and eating are crucial to our understanding of food webs. The use of signals to detect predators has strong relevance for prey survival. The black sea urchin Echinometra lucunter cohabits with the green sea urchin Lytechinus variegatus and a generalist echinivorous predator, the cushion sea star Oreaster reticulatus. Because black sea urchins evolved under the same predation pressure as green sea urchins and, consequently, were exposed to the same sensory cues, they are hypothesised to be able to detect echinivorous predator odours and chemical cues from green sea urchins as well as from injured conspecifics to elicit antipredator responses. Black sea urchins responded strongly to predators fed on a diet of conspecifics, showed a weak response to predators fed on green sea urchins and did not respond to a starved predator. The failure of black sea urchins to respond to hungry cushion sea stars probably increases their risk of being consumed. Black sea urchins, however, responded strongly to injured conspecific and, to a lesser degree, to heterospecific prey. In addition to the dilution effect imposed by the habit of living in dense assemblages, black sea urchins use the defence strategy of detecting an upcoming threat via chemical cue from injured prey when cues emanating from the echinivorous predator itself are not detectable.
Keywords: Chemical communication; Defensive behaviour; Echinoderms; Predation risk; Predator-prey system; Sympatric prey